1985
DOI: 10.1001/jama.1985.03360220062029
|View full text |Cite
|
Sign up to set email alerts
|

Normal Immune Response to Hepatitis B Vaccine in Patients With Down's Syndrome

Abstract: Institutionalized patients with Down's syndrome (DS) are uniquely predisposed to develop chronic hepatitis B infection following exposure. Therefore vaccination is particularly warranted, but there have been concerns that these individuals may react suboptimally. We examined the immune responses of 62 institutionalized patients with DS to 20 and 40 micrograms of hepatitis B vaccine inactivated (Heptavax-B) over one year. The subjects were matched by weight, age, and sex. Seroconversion rates and levels of anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

1985
1985
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(8 citation statements)
references
References 26 publications
1
6
1
Order By: Relevance
“…Correspondingly, these anti-HBs responses were significantly greater than those observed by us in a previous vaccine trial in which Down's syndrome clients were given 20 pg of HEPTAVAX-B [Troisi et al, 19851. As anticipated [Hollinger et al, 1982;Troisi et al, 1985;Zahradnik et al, 1985;Hollinger et al, 19861, seroconversion rates and geometric mean anti-HBs levels decreased as dosage was reduced. In addition to the excellent peak antibody levels generated by this vaccine 1 month after the last inoculation, the rapid anti-HBs response that occurred in 80% of the subjects receiving the 20 pg dose 2 weeks after the initial injection suggests that this immunogen may be beneficial in postexposure prophylaxis where the early development of immunity is advantageous.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Correspondingly, these anti-HBs responses were significantly greater than those observed by us in a previous vaccine trial in which Down's syndrome clients were given 20 pg of HEPTAVAX-B [Troisi et al, 19851. As anticipated [Hollinger et al, 1982;Troisi et al, 1985;Zahradnik et al, 1985;Hollinger et al, 19861, seroconversion rates and geometric mean anti-HBs levels decreased as dosage was reduced. In addition to the excellent peak antibody levels generated by this vaccine 1 month after the last inoculation, the rapid anti-HBs response that occurred in 80% of the subjects receiving the 20 pg dose 2 weeks after the initial injection suggests that this immunogen may be beneficial in postexposure prophylaxis where the early development of immunity is advantageous.…”
Section: Discussionsupporting
confidence: 64%
“…Previous studies with intact particle vaccines had clearly documented that dose/kg body weight is an important variable in persons under the age of 30 years [Troisi et al, 1985;Zahradnik et al, 19851. Other data have suggested that obesity may adversely affect the immune response, especially in persons receiving the vaccine in the gluteal region weber McLean et al, 19851.…”
Section: Discussionmentioning
confidence: 99%
“…One hundred per cent HBsAb responders were found in both groups at the third dose of vaccine. This percentage is higher than that found by Troisi et al (1985) and by Heijtink et al (1984) in adult individuals with either 20 or 40 fig of hepatitis B vaccine inactivated (Heptavax B, and H-B-Vax, respectively). This may depend either on the different types of vaccine used in the present study, and on the younger age of patients as well, in keeping with the trend of a better immune response to hepatitis B vaccine reported in the younger age groups.…”
Section: Discussioncontrasting
confidence: 59%
“…This point has recently been emphasized (Greeh, 1988(Greeh, ,1989Tyrer et a/., 1989), and it has been agreed that increased susceptibility and greater likelihood of long-term carriage for hepatitis B would be an indication for routine early immunization of DS children, even if they live at home and attend mainstream schools. Nevertheless, apart from a few studies of adult and adolescent institutionalized DS individuals (Wahl et al, 1983;Heijtink et al, 1984;Troisi et al, 1985;Green, 1989;Van Damme et al, 1990), no particular studies on the outcome of hepatitis B vaccination in DS children (both institutionalized and living at home) are avail-able. Since some doubts still exist on the effectiveness of early hepatitis B vaccination in a pediatric immuno-compromised group (Renner et al, 1985) the present authors started a pilot study of the efficacy of hepatitis B vaccination in a sample of DS children in their department, vaccination in terms of looking at the number and percentage of HBsAb seroconversion that could be achieved.…”
Section: Introductionmentioning
confidence: 99%
“…None of the three articles that dealt with vaccination response met the criteria for this study, Journal of Intellectual Disability Research two because of the very small numbers of patients, and one because it gave no data on which odds ratios could be calculated. All authors (Troisi et al 1985;Avanzini et al 1988;Van Damme et al 1990) concluded that people Down's syndrome had a normal response to vaccination.…”
Section: Hepatitismentioning
confidence: 99%